LOGIC VERSUS MAGIC IN MICHAEL ROBERT JOHNSON'S SHERLOCK HOLMES HOLIDAY MOVIE (2009): A SOCIOLOGICAL APPROACH - SETIAWAN, NAI (2011)
The major problem in this research paper is to explain How Logic versus Magic reflected in Michael Robert Johnson's Sherlock Holmes Holiday is. The purposes of this research paper are to analyze Michael Robert Johnson's Sherlock Holmes Holiday Movie (2009) based on the structural elements of the movie. To describe Logic versus Magic reflected in Michael Robert Johnson's Sherlock Holmes Holiday Movie (2009) based on sociological approach. The object study is Sherlock Holmes Holiday movie that the screen play is by Michael Robert Johnson. It is using by sociological approach. In analyzing this study, the writer uses qualitative methodology of research and sociological approach. The Primary data source of this research is the movie Sherlock Holmes Holiday movie that screen play by Michael Robert Johnson. The secondary data sources are the author's biography, essay, comment, homepage, and website about the movie and other relevant sources. Having analyzed this research paper, the writer presents four conclusions. First, the Sherlock Holmes movie is based of the novel of Sherlock Holmes that written by Sir Arthur Conan Doyle. Second, the director success makes this movie become the popular adventure mystery movie. Third, in Sherlock Holmes movie the director reflected logic versus Magic with the major character. The logic is Sherlock Holmes that has deductive think, and then the magic is Lord Blackwood. Fourth, the director shows to the audience from this movie for the people in this world, to think logic.